Relationship Between Waist-Hip Ratio (WHRC) And Prementrual Syndrome (PMS) - Afitsya Salsa Ayudi; Teta Puji Rahayu; Agung Suharto; Nuryani Nuryani (International Journal of Advanced Health Science and Technology, 2025)
Premenstrual Syndrome (PMS) is a common health problem experienced by adolescent girls, characterized by physical, emotional, and psychological symptoms related to the menstrual cycle. Waist-to-Hip Circumference Ratio (RLPP), which is a comparison between waist circumference and pelvis, is thought to play a predictive role in the incidence of STDs. This study uses an observational analytical design with a cross sectional approach. A simple random sampling sample was taken from 140 respondents. RLPP is measured directly, while PMS is assessed using the Shortened Premenstrual Assessment Form (SPAF) questionnaire. Data analysis was carried out by Chi-Square test. Most of the respondents with normal RLPP experienced mild PMS (65 female students), while the majority of respondents with high RLPP experienced moderate PMS (25 female students). The results of the statistical test showed a value of p = 0.000, indicating a significant relationship between RLPP and PMS. There is a meaningful association between RLPP and the incidence of PMS. RLPP above normal limits not only reflects the risk of metabolic syndrome, but is also associated with reproductive and emotional health disorders in adolescents. Promotive interventions such as increased physical activity, healthy diets, and monitoring of nutritional status are important to be implemented in educational and family settings.